Evaluating the taphonomic consistency of microvertebrate assemblages at Natural Trap Cave, Wyoming, USA. (20th February 2023) - McGuire, Jenny L.; Woodruff, Aaron; Iacono, Jennifer; Sethna, Jadyn M.; Schap, Julia A.; Redman, Cory M.; Meachen, Julie A.
Abstract: Paleontological sites composed of small vertebrate specimens can contain hundreds-of-thousands of identifiable fossils, which can reveal community responses to environmental and trophic changes. However, the composition of these communities may be skewed if the taphonomic signatures of the deposits change over time and across strata. Here, we discuss the taphonomic processes that led to dense deposits of microvertebrate fossils at Natural Trap Cave, Wyoming, USA. We then evaluate the nature and consistency of the taphonomic signature across stratigraphic layers using bone breakage rates and bone processing information. Natural Trap Cave is a pitfall cave that has an excellent record of vertebrate communities over the last 35, 000 years. Along the North Wall of the excavation site, microvertebrate fossils form a dense accumulation, raining down from a packrat ( Neotoma ) nest located ∼20 m above the floor of the cave. Using the breakage rates of micromammal limb bones, we evaluate whether the accumulation mechanism appears consistent across strata. We demonstrate that the variation in breakage rates from Natural Trap Cave's strata cluster together when compared to breakage rates for different predator types (mammalian carnivores, raptors, and owls). We then demonstrate that the variation in breakage rates from the three strata is less than would be expected if it were the result of a change in major predator type across the strata. Our analysis of depositional taphonomy at Natural Trap Cave provides confidence in the reliability of the microvertebrate community record, paving the way for future paleoecological analyses.